1997
DOI: 10.1002/elps.1150181018
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nonisotopic capillary electrophoresis‐based method for measuring glomerular filtration rate

Abstract: The conditions for quantitative measurement of nonisotopic iothalamate meglumine (Conray) in urine and plasma by capillary zone electrophoresis (CE) have been developed. The impetus for developing this methodology was to replace the traditional [125I]iothalamate glomerular filtration rate (GFR) marker assay, a routine tool in the measurement of kidney function. This new approach for measuring kidney function is attractive since it avoids the cost of administration of radioisotopic compounds to patients, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…High-sensitivity methods that are capable of reliably measuring CRP concentrations Յ0.15 mg/L (approximately the first and second percentiles of CRP distribution in healthy adults) have, therefore, been developed (7,8 ). Furthermore, an algorithm for risk assessment of future coronary events that combines both CRP concentration and total cholesterol:HDL-cholesterol ratio has been proposed (9 ). According to this algorithm, an individual's risk can be estimated with use of quintiles of CRP and lipids derived from ongoing population-based surveys.…”
Section: Capillary Electrophoresis Methods To Measure P-aminohippuric mentioning
confidence: 99%
See 1 more Smart Citation
“…High-sensitivity methods that are capable of reliably measuring CRP concentrations Յ0.15 mg/L (approximately the first and second percentiles of CRP distribution in healthy adults) have, therefore, been developed (7,8 ). Furthermore, an algorithm for risk assessment of future coronary events that combines both CRP concentration and total cholesterol:HDL-cholesterol ratio has been proposed (9 ). According to this algorithm, an individual's risk can be estimated with use of quintiles of CRP and lipids derived from ongoing population-based surveys.…”
Section: Capillary Electrophoresis Methods To Measure P-aminohippuric mentioning
confidence: 99%
“…Measurement of PAH in urine and plasma by HPLC has been described (4 -7 ), but it requires relatively large sample volumes and time-consuming extraction procedures. We recently found that capillary electrophoresis (CE) is an efficient, inexpensive, and reliable method for measurement of the nonradiolabeled iothalamate in urine and plasma samples for the assessment of glomerular filtration rate (8,9 ). Analysis by CE is analytically faster than standard HPLC or colorimetric assays, requires less reagent preparation and smaller sample size, minimizes drug interferences, and improves test turnaround time.…”
mentioning
confidence: 99%
“…GFR can be more precisely and accurately measured using exogenous compounds that are freely cleared by the kidney. Iothalamate is a radiopaque imaging media that has been used extensively in research and clinical practice for GFR determination (5)(6)(7)(8). 125 I-labeled iothalamate has been used for GFR measurement (9,10 ).…”
mentioning
confidence: 99%
“…To avoid the use of radioactive materials, laboratory methods have been developed to quantify nonradioactive iothalamate using HPLC (5,6,(11)(12)(13) or capillary electrophoresis (CE) (7,8 ) coupled with ultraviolet (UV) detection systems. The HPLC-UV methods require long run times, limiting sample throughput, and the CE-UV methods can be susceptible to interference (7,8 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation